LANGUAGE ACQUISITION OF 4-5-YEAR-OLD TODDLERS: INDONESIAN AND ENGLISH IN THE COVID-19 ERA - Zurriyati Zurriyati; Alemina Br Perangin-angin; Fika Emylia Effendi; Khairunnisa Tambunan (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2023)
The novel coronavirus, also known as COVID-19, has caused a global pandemic, resulting in widespread social distancing measures for all ages, including toddlers. Such policies have significantly impacted toddlers' language acquisition, particularly in terms of their lack of interaction with peers and teachers at Early Childhood Education (PAUD) schools. In light of this, the current study sought to discover how toddlers aged 4-5 fared regarding language acquisition during their early childhood. To accomplish the goal mentioned earlier, the authors of this study attempted to provide maps with animal and fruit images in both Indonesian and English. Toddlers have had fewer opportunities to interact with their peers at school due to the current circumstances, which include the spread of the new coronavirus and strict social restrictions, resulting in a decrease in vocabulary acquisition through minimal interaction. As a result, this study was carried out to evaluate the language acquisition process of early childhood students. The current study used a descriptive research design with an early childhood student sample. This study's data collection methods included observation and interviews. The results of this study revealed that, while the toddlers could name the pictures given to them when they were younger, their English language skills remained very low.Novel coronavirus, juga dikenal sebagai COVID-19, telah menyebabkan pandemi global, mengakibatkan tindakan jarak sosial yang meluas di segala usia, termasuk balita. Kebijakan tersebut berdampak signifikan pada penguasaan bahasa balita, terutama dalam hal kurangnya interaksi dengan teman sebaya dan guru di sekolah Pendidikan Anak Usia Dini (PAUD). Sehubungan dengan hal ini, penelitian saat ini berusaha untuk menemukan bagaimana nasib balita berusia 4-5 tahun dalam hal penguasaan bahasa selama masa kanak-kanak mereka. Untuk mencapai tujuan tersebut di atas, penulis penelitian ini mencoba menyediakan peta dengan gambar hewan dan buah dalam bahasa Indonesia dan bahasa Inggris. Balita memiliki lebih sedikit kesempatan untuk berinteraksi dengan teman sebayanya di sekolah karena keadaan saat ini, termasuk penyebaran virus corona baru dan pembatasan sosial yang ketat, mengakibatkan penurunan perolehan kosa kata melalui interaksi yang minimal. Oleh karena itu, penelitian ini dilakukan untuk mengevaluasi proses pemerolehan bahasa siswa usia dini. Penelitian ini menggunakan desain penelitian deskriptif dengan sampel siswa PAUD. Metode pengumpulan data penelitian ini meliputi observasi dan wawancara. Hasil penelitian ini mengungkapkan bahwa, meskipun balita dapat menyebutkan gambar yang diberikan kepada mereka saat masih kecil, kemampuan bahasa Inggris mereka masih sangat rendah.